Velopharyngeal videofluoroscopy: Providing useful clinical information in the era of reduced dose radiation and safety. (October 2016) - Ysunza, Pablo Antonio; Bloom, David; Chaiyasate, Kongkrit; Rontal, Matthew; VanHulle, Rachel; Shaheen, Kenneth; Gibson, Donald
Abstract: Background: The state of the art for correcting velopharyngeal insufficiency (VPI) is a surgical procedure which is customized according to findings on imaging procedures: multiplanar videofluoroscopy (MPVF) and flexible videonasopharyngoscopy (FVNP). Recently, the use of MPVF has been challenged because of the potential risk of using ionizing radiation, especially in children. Objective: To study whether using a protocol for performing MPVF can effectively decrease radiation dose in patients with VPI while providing useful information for planning surgical correction of VPI in combination with FVNP. The methodology used for performing the imaging procedures is described as well as the effectiveness of the surgical procedure. Material and methods: Eighty - nine patients (Age range = 3–17 years; median = 5.5 years) with VPI resulting from multiple etiologies were studied. All patients underwent MPVF and FVNP for planning surgical correction of VPI. Radiation dosage data in each case was recorded. Forty of the 89 patients also completed a postoperative evaluation. Eleven out of the remaining 49 patients have not completed a postoperative evaluation and 38 patients are still pending surgical correction. Results: Radiation dosage ranged from 1.00 to 8.75 miliSieverts (mSv); Mean = 2.88 mSv; SD = 1.575 mSv. Preoperative nasometry demonstrated mean nasalance ranging from 41%–95%; Mean = 72.30; SD = 4.54. Postoperatively mean nasalance was within normal limits in 36 (90%) out of 40 cases, ranging from 21% to 35%; Mean = 28.10; SD = 5.40. Nasal emission was eliminated postoperatively in all cases. Conclusion: MPVF provides useful information for planning the surgical procedure aimed at correcting VPI. The combination of MPVF and FVNP is a reliable procedure for assessing velopharyngeal closure and to surgically correcting VPI with a highly successful outcome.